Day of the Dead in the USA : the migration and transformation of a cultural phenomenon - Marchi, Regina M., 1965- (Rutgers University Press, 2009)
Honoring relatives by tending graves, building altars, and cooking festive meals has been an honored tradition among Latin Americans for centuries. The tribute, "el Dia de los Muertos," has enjoyed renewed popularity since the 1970s when Latino activists and artists in the United States began expanding "Day of the Dead" north of the border with celebrations of performance art, Aztec danza, art exhibits, and other public expressions. Focusing on the power of ritual to serve as a communication medium, Regina M. Marchi combines a mix of ethnography, historical research.
Keywords: All Souls' Day -- United States.; United States -- Social life and customs.; United States -- Religious life and customs.; Jour des morts -- États-Unis.; États-Unis -- Mœurs et coutumes.; SOCIAL SCIENCE -- Holidays (non-religious); SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; All Souls' Day; Manners and customs; United States